2019
DOI: 10.1016/j.toxrep.2019.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic pitfalls and laboratory test interference after hydroxychloroquine intoxication: A case report

Abstract: HighlightsHydroxychloroquine overdose can cause hypokalemia.Hydroxychloroquine overdose can result in electrocardiographic abnormalities.Hydroxychloroquine can interfere with urine chemistry and drug screening assays.Urine concentrations of hydroxychloroquine can exceed 500 mg/L in acute overdose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
5

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 38 publications
1
45
0
5
Order By: Relevance
“…HCQ alone can cause QT prolongation and is known to cause torsades de pointes, especially among patients with a history of cardiac dysfunction. 60 The use of HCQ in patients with COVID-19 has been associated with cardiac toxicity. 19 It is known that patients with a history of cardiovascular disease are more likely to develop into severe cases, as COVID-19 can promote acute cardiac injury.…”
Section: Discussionmentioning
confidence: 99%
“…HCQ alone can cause QT prolongation and is known to cause torsades de pointes, especially among patients with a history of cardiac dysfunction. 60 The use of HCQ in patients with COVID-19 has been associated with cardiac toxicity. 19 It is known that patients with a history of cardiovascular disease are more likely to develop into severe cases, as COVID-19 can promote acute cardiac injury.…”
Section: Discussionmentioning
confidence: 99%
“…However, the efficiency and safety of CQ and HCQ for treating COVID-19 remain uncertain due to recent controversial results [87], especially its' potential cardiac toxicity. CQ/HCQ alone can cause QT prolongation and is known to cause torsades de pointes, especially among patients with a history of cardiac dysfunction and when administered in combination with other drugs such as lopinavir/ritonavir (LPV/r); [88]. It was reported that 30% of patients treated with HCQ + azithromycin developed new QT prolongation of > 40 ms [89].…”
Section: Treatment Suggestionsmentioning
confidence: 99%
“…Case reports have noted prolonged QTc values with hydroxychloroquine toxicity. [73][74][75][76][77][78] In a study of 85 patients with connective tissue disorders who were receiving hydroxychloroquine, the investigators concluded that QT intervals did not appear to be different from what would be considered normal in these patients. 79 Recently there are emerging QT data from 84 patients with SARS-CoV-2 infection treated with a combination of hydroxychloroquine and azithromycin.…”
Section: Effects Of Chloroquine and Hydroxychloroquine On Qtc Prolongmentioning
confidence: 99%